Redefining Classical Theory of Humours (Akhlat) with Emphasis on Khilt-e-Sauda (Black Bile) Through its Physiological Role - Riaz, Arshi; Ali, Ferasat; Noor, Huma; Rizvi, Asim (Current Traditional Medicine, 2024)
Background: According to Hippocrates, Akhlat is of four types, i.e., Dam (Blood), Balgham (Phlegm), Safra (Yellow Bile), and Sauda (Black Bile). The correct proportion of these fluids in the body, in terms of quality and quantity, leads to health, while their irregular distribution leads to diseases. The argument presented in this paper will encompass both Tabayi and Ghair Tabayi Sauda.Objective: However, in light of recent advances in the area of molecular biology and biochemistry of the human body, we aim to discuss Sauda as a Khilt in the context of human physiology. We propose that the chemico-biological / physiological role of the molecule rather than its structure will define its placement in Khilt-e-Sauda.Conclusion: Chemico/biological role of the molecule may change with the physiological context, and hence the placement of the molecule previously included in the Khilt-e-Sauda, may or may not remain in that categorization at that point in time in that physiological state.
Keywords: Unani